2020
DOI: 10.20473/mgi.v15i1.31-37
|View full text |Cite
|
Sign up to set email alerts
|

HUBUNGAN PERILAKU PICKY EATER DENGAN TINGKAT KECUKUPAN PROTEIN DAN LEMAK PADA ANAK PRASEKOLAH <br><i>[Correlation of Picky Eater Behavior to Protein and Fat Intake in Adequacy Pre-School Children] </br></i>

Abstract: Anak prasekolah membutuhkan zat gizi yang adekuat untuk pertumbuhan yang pesat. Perilaku pilih-pilih makan sering terjadi pada anak prasekolah. Perilaku ini akan mempengaruhi jenis makanan yang dikonsumsi menjadi kurang beragam. Apabila hal ini terjadi terus menerus akan mempengaruhi tingkat kecukupan zat gizi dan status gizi. Penelitian ini bertujuan untuk menganalisis hubungan perilaku picky eater dengan tingkat kecukupan protein dan lemak pada anak prasekolah. Penelitian ini merupakan penelitian observasion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…According to research, the majority of people who have experienced picky eating problems as children are boys. Preschool children generally show picky eating habits, according to previous research 9 . This shows zero fundamental differences between girls and boys.…”
Section: Resultsmentioning
confidence: 56%
“…According to research, the majority of people who have experienced picky eating problems as children are boys. Preschool children generally show picky eating habits, according to previous research 9 . This shows zero fundamental differences between girls and boys.…”
Section: Resultsmentioning
confidence: 56%
“…Preschool children need protein to support growth and development. 25 Fat is needed by the body to absorb fat-soluble vitamins, and fat is a crucial source for growth, but if the amount is excessive for a long time will cause excess fat accumulation in the body and the risk of obesity. 25 All children consumed fat in the form of whole cream milk and vegetable oil more than once a day.…”
Section: Discussionmentioning
confidence: 99%
“…25 Fat is needed by the body to absorb fat-soluble vitamins, and fat is a crucial source for growth, but if the amount is excessive for a long time will cause excess fat accumulation in the body and the risk of obesity. 25 All children consumed fat in the form of whole cream milk and vegetable oil more than once a day. The questionnaire results found that children rarely consume fast food, soft drinks, and fried foods.…”
Section: Discussionmentioning
confidence: 99%
“…World Health Organization (WHO) mengatakan bahwa kasus anak usia prasekolah yang mengalami underweight di dunia sebesar 15,7% serta anak usia prasekolah overweight sebanyak 6,6% 2 . Data nasional menyebutkan prevalensi berat-kurang pada tahun 2013 merupakan 19,6%, terdiri dari 5,7% gizi buruk dan 13,9% gizi kurang dan data dari Riskesdas menampilkan pada tahun 2018 proporsi gizi kurang pada balita senilai 13,8 % yang di mana target proporsi nasional adal 17% 3 .…”
Section: Pendahuluanunclassified